Rancang Bangun Alat Penyiram Sayuran Hidroponik Menggunakan Arduino Mega 2560 - Kusumo, Bayu; Azis, Nur (STMIK Budi Darma, 2021)
Activities suitable for planting with hydroponic systems in the midst of covid 19 pendemi are in great demand by utilizing limited land. One of the elements in suitable planting activities is water, because 70 percent of the molecules in plants are water. Water serves as the raw material of plants in the process of photosynthesis and can also keep plant moisture from withering. Currently the method of watering plants is still done manually by checking the condition of the soil, if the soil condition is dry then the new water pump is turned on for watering. But the method is considered less effective because it requires farmers to do regular checks and should not forget so that the soil does not dry so that the plants do not wither. To answer these problems in this study want to provide certainty how the plant gets enough water. One of the efforts that can be done is to make an automatic watering tool that without having to take time so as to give an efficient impact. The tool is made using Arduino Mega 2560 Components that serve as controllers in the watering system with the help of smartphones for remote control.